2022
DOI: 10.1007/s42773-022-00146-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochar for the removal of contaminants from soil and water: a review

Abstract: Biochar shows significant potential to serve as a globally applicable material to remediate water and soil owing to the extensive availability of feedstocks and conducive physio-chemical surface characteristics. This review aims to highlight biochar production technologies, characteristics of biochar, and the latest advancements in immobilizing and eliminating heavy metal ions and organic pollutants in soil and water. Pyrolysis temperature, heat transfer rate, residence time, and type of feedstock are critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(131 citation statements)
references
References 156 publications
1
89
0
2
Order By: Relevance
“…Orange peel and sugarcane bagasse were used to obtain carbonaceous structures such as activated carbons and carbon foams for their application in the removal of heavy metal ions. The data set of this work shows information on the characterization and evaluation of these carbon materials that can be used as adsorbent materials, confirming recent reports [2] , [3] , [4] , [5] . Fig.…”
Section: Data Descriptionsupporting
confidence: 87%
See 1 more Smart Citation
“…Orange peel and sugarcane bagasse were used to obtain carbonaceous structures such as activated carbons and carbon foams for their application in the removal of heavy metal ions. The data set of this work shows information on the characterization and evaluation of these carbon materials that can be used as adsorbent materials, confirming recent reports [2] , [3] , [4] , [5] . Fig.…”
Section: Data Descriptionsupporting
confidence: 87%
“…In general, pyrolysis showed higher ash content, higher surface area development due to the loss of carbon components at high temperatures, and higher micropore volume, respectively [4] . The chemical activation consisted in the surface modification using an acid treatment; this activation, increases the specific area and generates a variety of pores, it adds chemical groups such as oxygen and nitrogen [5] . Two activation temperatures were used during the production of AC, 500 °C and 700 °C, and phosphoric acid (H 3 PO 4 at 85 wt.%) was used as chemical reagent (Sigma Aldrich, 85% purity).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The highly porous structure of biochar makes it ideal for use as an absorbent [ 14 , 16 ]. The detection of toxic heavy metals is always accompanied by a procedure of absorption.…”
Section: The Role Of Biochar In the Fabrication Of Electrochemical Se...mentioning
confidence: 99%
“…The study of biochar on a large scale started in 2010 and moved to a reactivity exploration stage from 2014; the first works were reported in 1999 [ 6 ]. In order to better summarize the existing research results and to carry out more in-depth research on biochar, many review papers were published in the past decade [ 12 , 13 , 14 , 15 , 16 ]. Some comprehensive reviews identified biochar as a functional and novel material, in the context of a general discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of biochar may improve its adsorption capability for nitrate by weakening the electrostatic repulsion between biochar and nitrate anions. Popular modification approaches consist of the protonation of negatively charged functional groups or loading of metal oxide/hydroxide particles on the biochar surface [26]. In particular, the supported iron oxide/hydroxide on biochar have been frequently reported due to their excellent properties, such as improved binding sites and point of zero charge [27].…”
Section: Introductionmentioning
confidence: 99%